TATA KELOLA PROGRAM CORPORATE SOCIAL RESPONSIBILITY (CSR) MELALUI KONSEP COLLABORATIVE GOVERNANCE DALAM MENUNJANG PROGRAM PEMBANGUNAN DAERAH - Putri Andayani Br Sitepu; Rio Yusri Maulana (Jurnal Ilmu Pemerintahan Widya Praja, 2021)
Each company apart from increasing financial benefits through its operational activities also has an obligation to carry out social programs for the environment and surrounding communities. This concept is known as the company's Corporate Social Responsibility (CSR) program. The use of the CSR program for the implementation of government development tasks can be described through the concept of Collaborative Governance or the concept of partnership in government. This paper will analyze the use of CSR programs carried out by the Jambi City government through the concept of Collaborative Governance in order to accelerate development by taking into account the government's priority programs. The research method used is a descriptive qualitative approach. Data collection was carried out through observation, interviews and documentation. Then the data were analyzed by examining the findings, presenting the data, and drawing conclusions. The results show that the Jambi City Government has implemented the concept of collaborative governance in implementing and utilizing CSR funds for development programs through the CSR forum. Keywords: Corporate Social Responsibility; Collaborative Governance; Regional Development.